i am getting little bit confuse in **Associative property**and **Distributive property. please explain it**

**Associative Property of Numbers**

For example, let us consider three numbers 5, 10 and 15.

Now, (a + b) + c = (5 + 10) + 15 = 15 + 15 = 30

and a + (b + c) = 5 + (10 + 15) = 5 + 25 = 30

Hence, (a + b) + c = a + (b + c)

If 'a', 'b' & 'c' are three rational numbers, then (a × b) × c = a × (b × c)

You can also verify this property by considering any numerical value of a, b and c.

**Distributive Property:**

**Distributive property for multiplication over addition**

*a *× (*b *+* c*)* = a *×* b *+* a *×* c*

*a*× (

*b*+

*c*) means that first of all we need to add

*b*and

*c*, then this result is multiplied with

*a*.

Multiply* a* with *b* and *a* with *c*. The sum of the products, *a *×* b *+* a *×* c* is same as the *a *× (*b *+* c*).

Consider a, b, c equals to 2, 4 and 6 respectively.

Now, *a *× (*b *+* c) = 2 *× (*4 *+* 6) = 2 *× 10 = 20

and * a *×* b *+* a *×* c = 2 *×* 4 *+* 2 *×* 6 = 8 + 12 = 20*

*a*× (

*b*+

*c) = a*×

*b*+

*a*×

*c*

**Distributive property for multiplication over subtraction**

*a*× (

*b*–

*c*)

*= a*×

*b*–

*a*×

*c*

*a *× (*b *–* c*) means that first of all we need to subtract *c* from *b*, then this result is multiplied with *a*.

Multiply* a* with *b* and *a* with *c*. The difference of the products, *a *×* b *–* a *×* c* is same as the *a *× (*b *–* c*).

You can also verify this property by considering any numerical value of a, b and c.

**
**